The puzzling long-term relationship between de jure and de facto judicial independence - Bernd Hayo; Stefan Voigt (Philipps-University Marburg, School of Business and Economics, 2018)
We study the long-term and dynamic relationship between de jure and de facto judicial independence using a large panel dataset covering 50 countries over a period of 50 years. Our analysis shows a negative relationship between these variables, a sharp contrast to the prevailing theoretical view in the literature. However, the magnitude of the relationship is small. The negative association between the two variables is driven by OECD countries, whereas a positive one can be found for non-OECD countries. We discover no evidence of reverse causality running from de facto to de jure judicial independence.
Keywords: D72; D78; K42; 330; Judicial independence; de facto; de jure; long-term panel data analysis; cointegration; Granger causality